2021
DOI: 10.18632/aging.202605
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prognostic nomogram for predicting in-hospital mortality of COVID-19: a multicenter retrospective cohort study of 4086 cases in China

Abstract: To establish an effective nomogram for predicting in-hospital mortality of COVID-19, a retrospective cohort study was conducted in two hospitals in Wuhan, China, with a total of 4,086 hospitalized COVID-19 cases. All patients have reached therapeutic endpoint (death or discharge). First, a total of 3,022 COVID-19 cases in Wuhan Huoshenshan hospital were divided chronologically into two sets, one (1,780 cases, including 47 died) for nomogram modeling and the other (1,242 cases, including 22 died) for internal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Therefore, LDH may help detecting tissue damage in the onset of COVID-19 infection. Similar to our study, some previous studies reported LDH as a predictive marker for severe illness [ 20 , 24 , 27 , 31 , 32 ]. Troponin I is also one of the predictors in our nomogram.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, LDH may help detecting tissue damage in the onset of COVID-19 infection. Similar to our study, some previous studies reported LDH as a predictive marker for severe illness [ 20 , 24 , 27 , 31 , 32 ]. Troponin I is also one of the predictors in our nomogram.…”
Section: Discussionsupporting
confidence: 92%
“…In the literature, there are studies proposing nomograms and/or different models to predict serious illness or death in COVID-19 patients [ 19 , 21 , 22 , 24 , 25 , 35 37 ]. Age was reported as a predictor for severe COVID-19 or mortality in previous studies and is included in most of the prediction models [ 16 – 21 , 24 , 25 , 32 , 35 , 38 , 39 ]. We found an increased risk of severe infection requiring ICU admission in the patients 56.5 years of age and older.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Totally included in this multi-center prospective cohort study were real-time reverse transcription polymerase chain reaction (RT-PCR)-confirmed older COVID-19 patients (age ≥ 60) who were discharged from Huoshenshan Hospital and Taikang-Tongji Hospital (both in Wuhan, China) between Feb 12 and Apr 10, 2020. 8 All discharged patients met the uniform discharge criteria of the World Health Organization interim guidance. 27 The follow-up was conducted between Mar 1, 2021 and Mar 20, 2021.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…5 Both the occurrence and prognosis of COVID-19 were closely related to older age. [6][7][8] To date, series of studies have reported the potential short-to long-term sequelae of COVID-19 recovery, ranging from two months to one year. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] However, the older patients have not attracted enough attention and no specific studies quantified the temporal trends and associated risk factors for sequelae of COVID-19 in older patients, especially long-term sequelae.…”
Section: Introductionmentioning
confidence: 99%